2021
DOI: 10.1126/science.abi8976
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for target site selection in RNA-guided DNA transposition systems

Abstract: CRISPR-associated transposition systems allow guide RNA–directed integration of a single DNA cargo in one orientation at a fixed distance from a programmable target sequence. We used cryo–electron microscopy (cryo-EM) to define the mechanism that underlies this process by characterizing the transposition regulator, TnsC, from a type V-K CRISPR-transposase system. In this scenario, polymerization of adenosine triphosphate–bound TnsC helical filaments could explain how polarity information is passed to the trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
135
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(149 citation statements)
references
References 72 publications
13
135
1
Order By: Relevance
“…CASTs and other Tn 7 -like transposons integrate at a fixed distance downstream from their target sites ( 27 , 54 ) ( Fig. 1B ), which is typically ∼50 bp in CASTs and likely corresponds to the footprint of the transposition complex ( 30 , 33 , 55 , 56 ). In total, the LEs/REs were predicted for 352/523 (67%) of the previously reported CASTs.…”
Section: Resultsmentioning
confidence: 99%
“…CASTs and other Tn 7 -like transposons integrate at a fixed distance downstream from their target sites ( 27 , 54 ) ( Fig. 1B ), which is typically ∼50 bp in CASTs and likely corresponds to the footprint of the transposition complex ( 30 , 33 , 55 , 56 ). In total, the LEs/REs were predicted for 352/523 (67%) of the previously reported CASTs.…”
Section: Resultsmentioning
confidence: 99%
“…For type V-K systems, RNA-guided transposition relies on the CRISPR effector complex comprising Cas12k, a crRNA and a trans-activating RNA (tracrRNA), and three transposon proteins: the AAA+ ATPase TnsC, the transposase TnsB and the zinc-finger protein TniQ (Strecker et al, 2019). Biochemical and structural studies of a type V CAST system from Scytonema hofmanni (ShCAST) revealed that Cas12k-mediated DNA targeting depends on the intricate architecture of the tracrRNA that serves as a scaffold to correctly position Cas12k and the crRNA guide for the recognition of complementary targets (Park et al, 2021; Querques et al, 2021; Xiao et al, 2021). Upon binding to a 5’-GTN protospacer adjacent motif (PAM) in the target DNA, Cas12k initiates guide RNA hybridization that generates an incomplete R-loop structure, suggesting that further rearrangements occurring upon recruitment of the downstream transposon machinery are required to elicit further guide RNA-target DNA hybridization (Strecker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The growth in the 5’ to 3’ direction is stopped by TniQ binding at the filament end concomitantly connecting the TnsC filament with Cas12k. On the other filament end, the Mu-like transposase TnsB then starts to integrate the transposon 15 . In addition to the genes encoding transposase and effector proteins, all of these systems contain various numbers of cargo genes.…”
Section: Introductionmentioning
confidence: 99%
“…Targeting transposition by these CAST systems depends on the DNA-crRNA interaction facilitated by the effector protein Cas12k 11 . The TnsC transposon then forms helical polymers around the DNA supported by ATP binding 15 . The growth in the 5' to 3' direction is stopped by TniQ binding at the filament end concomitantly connecting the TnsC filament with Cas12k.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation